Santo Rio São Francisco: religiosidade popular na sacralidade do Rio São Francisco no imaginário dos pescadores do Sertão dos Gerais - Isidório, Maria Socorro (2010)
This dissertation analyzes the popular religiosity experienced by the old fishermen from Januária, a city in the north of Minas Gerais, in an attempt to understand certain sacred manifestations in the water of São Francisco river. Such religious experience was a significant foundation for constructing the identity of these men and their wives. The database consisted of the analytical historiography of Minas Gerais in regards to the State s dichotomic civilization process, as well as of interviews made with those fishermen. Oral history was used because it takes into account the histories of those men who had been excluded from capitalism and the official history. To comprehend the mystic of these waters, expressed in a symbolic language, we have used phenomenology. We have examined the construction of these fishermen s identity, which was established on contradictory historical basis, but erected in a body-soul unit solidified by sacred forces